Rapid‐deployment aortic valve replacement versus standard bioprosthesis implantation. Issue 6 (11th May 2017) - Ferrari, Enrico; Roduit, Christelle; Salamin, Pauline; Caporali, Elena; Demertzis, Stefanos; Tozzi, Piergiorgio; Berdajs, Denis; von Segesser, Ludwig
Abstract: Objective: To compare the outcome and the 1‐year hemodynamic results of the rapid‐deployment Intuity valve versus the Perimount Magna bioprosthesis in matched populations. Methods: Between March 2014 and May 2015, 32 patients underwent aortic valve replacement with the Intuity valve (Intuity‐group). These patients were compared to a matched population of Perimount valves implanted during the same period of time (Perimount‐group). Clinical data were compared and echocardiographic 1‐year follow‐up was performed. Results: There were more female patients in the Intuity‐group (47% vs 22%, p = 0.035); mean age was 78 ± 5.6 and 72.5 ± 6 years in the Intuity‐group and Perimount‐group (p < 0.001); coronary disease was more common in the Intuity‐group (65% vs 25%, p = 0.005). Other characteristics were similar. Implants were 100% successful. Mean cross‐clamp (50.3 ± 25 vs 53 ± 22 min, p = 0.004), cardiopulmonary bypass (68 ± 27 vs 72 ± 31.8 min; p = 0.006), and surgical times (156.8 ± 54 vs 165 ± 40 min; p = 0.018) were shorter with the Intuity despite more concomitant procedures. Mean valve size was 23.7 mm (Intuity‐group) and 24.1 mm (Perimount‐group); hospital mortality was zero (Intuity‐group) and 3% (Perimount‐group); new pacemaker implants were 6% (Intuity) and 3% (Perimount) (p = 0.55) and hospital stay was equivalent. Mean gradients were: 9.9 ± 3.4 (Intuity) versus 12.5 ± 3.8 mmHg (Perimount) (p = 0.022) at discharge and 9 ± 4 mmHg (Intuity) versus 14 ± 4 mmHg (Perimount) (p = 0.02) at follow‐up. At discharge, one Intuity valve had 3+ aortic insufficiency (AI) which was unchanged at 1 year and will require an intervention. Another patient had 1 + AI which progressed to 2+ at 1 year. There were no paravalvular leaks in the Perimount valves at discharge and follow‐up. Conclusion: Intuity valves showed lower gradients compared to Perimount valves with the same mean size. Paravalvular leaks identified at the time of implantation in Intuity valves need to be addressed at the time of surgery.